Is Duhuo Jisheng Tang containing Xixin safe? A four-week safety study - Hsieh, Shu-Ching (BioMed Central, 2010)
BACKGROUND: Though the nephrotoxicity and carcinogenicity of aristolochic acid (AA) are known, its safety in clinical usage is not clear. This study aims to evaluate the safety of Duhuo Jisheng Tang (DJT) in a four-week study to treat osteoarthritis (OA) of the knee. METHODS: A qualitative and quantitative investigations on DJT were conducted. A list of adverse events (AEs), complete blood counts, and liver and kidney function tests were measured for participants with knee OA at their scheduled hospital visits. Each detected AEs was independently assessed for severity and causality by site investigators (Chinese medical doctors) and study nurses. RESULTS: A total of 71 eligible subjects were included in the clinical study where 287 AEs were reported. DJT did not contain detectable aristolochic acid (AA) under thin-layer chromatography (TLC) analysis and gas chromatography coupled with mass spectrometry (GC-MS). There were no significant changes in liver or kidney functions. CONCLUSION: In four-week use of DJT, no renal tubular damage, no severe incidences of AEs and adverse drug reactions (ADRs) were observed. The present study obtained safety data from active surveillance of DJT.